(untitled) (Ciudades, 2018)
During the last few years, framed by the local development approaches, there has been created a new cultural read of territory. In this process, where territory, society and culture are the big protagonists, built heritage, due to its territorial referenciation, has an essential role on the reinforcing of new identities as well as in creating new spaces for development.